2014
DOI: 10.1002/syn.21744
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory tubercle neurons exhibit slow-phasic firing patterns during cocaine self-administration

Abstract: Electrophysiological recordings from the Olfactory Tubercle (OT) of rats trained to self‐administer cocaine were analyzed for distinct firing patterns. Observation revealed that neurons demonstrated changes in firing correlated with the calculated fluctuating levels of cocaine. These are the first electrophysiological data suggesting a role for the OT in drug self‐administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Besides, the NAc and OT, components of the ventral striatum, mediate reward processing similarly ( Striano et al, 2014 ; Millhouse and Heimer, 1984 ) and both are innervated by DAergic projections from the VTA. Although the NAc has been extensively studied, the OT has received much less attentions, in spite of the unique anatomical position.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the NAc and OT, components of the ventral striatum, mediate reward processing similarly ( Striano et al, 2014 ; Millhouse and Heimer, 1984 ) and both are innervated by DAergic projections from the VTA. Although the NAc has been extensively studied, the OT has received much less attentions, in spite of the unique anatomical position.…”
Section: Discussionmentioning
confidence: 99%
“…17 Therefore, VTA DA in the OT may also play a role in the neural correlates of reward. 10,[18][19][20] There is some evidence to suggest that despite similar patterns of VTA innervation, DA in the OT maybe critically involved in reward processing, potentially contributing more towards the processes underlying reward and drug addiction. 10,20,21 For these reasons, DA in the OT has begun to receive renewed attention from neuroscientists.…”
Section: Introductionmentioning
confidence: 99%
“…10,[18][19][20] There is some evidence to suggest that despite similar patterns of VTA innervation, DA in the OT maybe critically involved in reward processing, potentially contributing more towards the processes underlying reward and drug addiction. 10,20,21 For these reasons, DA in the OT has begun to receive renewed attention from neuroscientists. 10 Yet while DA is a key component of normal OT function, compared to other ventral striatal structures, DA transmission in the OT, its regulation, and functional roles are less known.…”
Section: Introductionmentioning
confidence: 99%
“…More recent work has shown that OT neural activity represents instrumental actions, as well as rewards themselves. First, and related to the above work by (Ikemoto, 2003), OT activity is modulated around the times animals self-administer cocaine (Striano et al, 2014). Second, work by our group found that OT units in water-motivated mice represent instrumental responding (licking) to obtain a fluid reward (Gadziola and Wesson, 2016) (Fig.…”
Section: Counterpoint: the Ventral Striatopallidummentioning
confidence: 79%